Ethical use of topical corticosteroids - Abir Saraswat (Wolters Kluwer Medknow Publications, 2014)
Dermatologists rely very heavily on corticosteroids for treating many common dermatoses. Concerns about their incorrect use are widely expressed both in lay public and specialist discourse. From the point of view of medical ethics, issues of autonomy, beneficence and non-maleficence are all raised frequently when we prescribe topical corticosteroids to our patients. We need to be aware of situations when conflicts between these issues arise and have a clear thought process about resolving them. This can only be achieved if we have a thorough understanding of the skin disease being treated coupled with expertise in the use of the varied potencies and available dosage forms of topical corticosteroids. A good understanding of human psychology and effective communication is also needed to use these agents optimally.